Obesity in Children with Leptin Receptor Gene Polymorphisms - Aleksandr Abaturov (Karolinum Press, 2021)
Introduction: The study of single nucleotide polymorphisms (SNPs) of the leptin receptor gene (LEPR) based on next generation genomic sequencing (NGS) data is becoming an increasingly important aspect of diagnosis, treatment and prevention of both metabolically healthy (MHO) and metabolically unhealthy obesity (MUO) phenotypes. Material and methods: 35 obese children 6-18 years old were examined by the NGS method with bioinformatic analysis. The main group (n = 18) was formed by children with MUO, according to the recommendations of the expert group of the National Heart, Lung, and Blood Institute. The control group (n = 17) was represented by children with MHO. Statistical methods were used: analysis of variance, Wald’s sequential analysis, Spearman’s correlation analysis, analysis of nominal data and multiple discriminant analysis. Results: 10 types of non-synonymous SNPs (rs3790435, rs1137100, rs2186248, rs70940803, rs79639154, rs1359482195, rs1137101, rs1805094, rs13306520, rs13306522) of the LEPR gene in obese children have been identified. Multiple discriminant analysis demonstrated that the following LEPR SNPs are of greatest importance in the development of MUO: rs3790435, rs13306522, rs13306520. Analysis of nominal data revealed significant differences in the groups for Copy number variation (CNV) rs3790435 of the LEPR gene. Wald’s analysis allowed us to identify 6 important predictors of MUO (І ≥ 0.5): 2 CNV rs3790435 (Relative Risk, RR = 2, Prognostic coefficient, PC = +2.76); male gender of the child (RR = 1.3, PC = +1.35); rs3790435 (RR = 1.9, PC = +2.76); hyperleptinemia more than 40.56 ng/ml (RR = 2, PC = +3); CNV rs1359482195 ≥ 3 (RR = 1.9, PC = +5.8); SNP of the LEPR gene ≥4 (RR = 3.8, PC = +5.8). Conclusion: Children with the genotype rs3790435 gene LEPR had signs of MUO more often.